Challenges and Implementation of Technology Integration: Basis for Enhanced Instructional Program (American Journal of Arts and Human Science, 2024)
This study focused on examining the challenges and implementation of technology in schools within the Baungon Districts, Division of Bukidnon, during the School Year 2023-2024. A validated questionnaire was administered to 289 respondents, and data analysis involved statistical tools and triangulation methods. The findings revealed diverse challenges, with Equity and Access being the highest and Infrastructure and Resources being the lowest. Despite these challenges, technology integration was observed, particularly in Communication and Instructional Integration. Significant relationships were identified between challenges and implementation, emphasizing the need for targeted interventions. In-depth interviews highlighted educators’ innovative strategies and commitment to delivering quality education through technology. Strategic interventions are necessary to address obstacles and enhance technology integration. Offering continuous professional development opportunities for teachers is crucial. The study provides insights for educational leaders to develop interventions and enhance technology integration, ultimately improving the educational experience for students.